The semiotics of configurations for the immanent design of interactive computational systems. (June 2017) - Cabitza, Federico; Mattozzi, Alvise
Abstract: In this paper the authors propose a novel semiotic approach to the design of interactive systems and computational systems, grounded in the most recent contributions within the debate around semiotic theory and analysis. This approach, that is here called Semiotics of Configurations (SoC), is proposed for its analytic power in describing material artifacts and settings with a purposely a-conceptualistic stance. The resulting analysis informs a kind of design that is aimed at reproducing and supporting the programs of action detected in the use of artifacts, as this use is "abducted" from the physical and material form of the artifacts themselves and from the observation of how content is transformed within and across them. This approach to design, called immanent design, has inspired a platform for the user-driven development and use of electronic documents and forms in cooperative and organizational domains. The framework is illustrated with a case drawn from a study performed in the domain of hospital work.